Loop-based Encoding and Decoding Algorithms for Distribution Network Reconfiguration - Kim, HyunWoo (IEEE Power & Energy Society General Meeting, 2024)
The traditional distribution network obtained sufficient effects through the local distribution network reconfiguration (DNR) that controls the adjacent switches, which are currently open. However, global DNR should be preceded for optimal operation and control of complex and congested active distribution networks by the growth of the distribution network and penetration of distributed energy resources (DERs). This study proposes encoding and decoding strategies to improve the search probability of global optimal configuration close to 100% through diminishing the search space in complex distribution networks. The en-coding algorithm systematically organizes the radial distribution network. The decoding algorithms reflect the current state of the network and present criteria for effectively searching the switches satisfying the radial topology. The validity and performance of the proposed algorithms are verified through the DNR case study using a genetic algorithm (GA) in the IEEE 33, 69, and 118 bus distribution networks. In addition, a two-stage search algorithm is implemented to improve the convergence speed while guaranteeing the global optimal solution.